Efektivitas Program Sekolah Penggerak dalam Meningkatkan Mutu Pendidikan di SMA Negeri 2 Makassar - Nisa, Nur Anniza Dwi Zari; Nurul Fausia; Ahlun Ansar; Arismunandar; Restiani (Pendidikan Al-Gafari, 2025)
This research evaluates the effectiveness of the Penggerak School Program at SMA Negeri 2 Makassar in improving the quality of education. The research background focuses on the challenges faced by the Indonesian education system, especially in implementing the Independent Curriculum. The research objective is to analyze five program interventions, including theme selection based on the Pancasila profile, curriculum development, learning innovation, and financial management. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation. The research results show that SMA Negeri 2 Makassar succeeded in implementing program interventions well, creating an inclusive learning environment and focusing on student character. This school is active in teacher training and the use of educational technology, as well as implementing projects related to Pancasila values. The conclusion of this research confirms that the Penggerak School Program can improve the quality of education through curriculum transformation and character strengthening, which has a positive impact on student achievement and the relevance of education in the era of globalization.